(untitled) (Scientific journal of the Fergana State University, 2025)
This article analyzes the work "Tanzil" of our great mystic compatriot Aziziddin Nasafi, its structure, the important mystical, philosophical, ethical, spiritual and educational issues contained in it. Also, the content and essence of Nasafi’s works, their style of writing, and the views on the topics reflected in them are briefly commented